Association of Average Daily Morphine Milligram Equivalents and Falls in Older Adult Chronic Opioid Users - Stephanie Hwang; Tamera D. Hughes; Joshua Niznik; Stefanie P. Ferreri (MDPI AG, 2024)
Opioids remain commonly prescribed in older adults, despite the known association with falls and fall-related injuries. This retrospective cohort study sought to determine the association of opioid use and falls in older adult opioid users. Using a one-year lookback period in electronic health records, daily morphine milligram equivalents (MMEs) were calculated using prescription orders. Fall history was based on patient self-reporting. A receiver operating characteristic (ROC) curve was used to identify the threshold of average daily MMEs at which the likelihood of falls was increased. Older opioid users were most often women and White, with 30% having fallen in the prior year. In ROC analyses (n = 590), the threshold where fall risk increased was 37 MMEs (p = 0.07). Older adults prescribed more than 37 MMEs daily may be at increased fall risk and should be targeted for deprescribing interventions. Additionally, analysis on patient characteristics and covariates suggest that sex, age, COPD, sleep apnea, cancer, and psychiatric conditions may indicate an increased risk of falls in older adults taking chronic opioids (p < 0.05). Multifactorial interventions may be needed to modify fall risk beyond medication use alone.